2015
DOI: 10.1099/mic.0.000106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inflammatory phenotype of Mycobacterium avium subspecies paratuberculosis using a novel cell culture passage model

Abstract: Understanding the pathogenic mechanisms of Mycobacterium avium subspecies paratuberculosis (MAP) and the host responses to Johne's disease is complicated by the multi-faceted disease progression, late-onset host reaction and the lack of available ex vivo infection models. We describe a novel cell culture passage model that mimics the course of infection in vivo. The developed model simulates the interaction of MAP with the intestinal epithelial cells, followed by infection of macrophages and return to the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…As Mtb, Map adapts to the intracellular environment in the macrophage, where the bacteria overcome exposure to cationic antimicrobial peptides, reactive oxygen species (ROS) and nutrient starvation, via the regulation of genes affecting its envelope's composition (Thirunavukkarasu et al, 2014). In fact, a different lipid profile was previously observed in the envelope of intracellular Map after 1 h of infection (Alonso-Hearn et al, 2010; Everman et al, 2015). The full significance of these alterations in lipid metabolism had to be yet revealed to identify the issues facing Map within host macrophages.…”
Section: Discussionmentioning
confidence: 78%
“…As Mtb, Map adapts to the intracellular environment in the macrophage, where the bacteria overcome exposure to cationic antimicrobial peptides, reactive oxygen species (ROS) and nutrient starvation, via the regulation of genes affecting its envelope's composition (Thirunavukkarasu et al, 2014). In fact, a different lipid profile was previously observed in the envelope of intracellular Map after 1 h of infection (Alonso-Hearn et al, 2010; Everman et al, 2015). The full significance of these alterations in lipid metabolism had to be yet revealed to identify the issues facing Map within host macrophages.…”
Section: Discussionmentioning
confidence: 78%
“…Once inside phagocytic cells, the ability of MAP to survive and replicate within these phagocytic cells plays a key role in pathogenesis ( 39 , 40 ). Moreover, use of a culture passage model showed that MAP lipid composition changes in macrophages developing a pro-inflammatory phenotype ( 41 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Unfortunately, the results obtained from the pipeline of determining host toxicity and vaccine efficacy from in vitro cultures and mouse models did not translate in a successful vaccine trial in ruminant hosts due to unappreciated differences in immunity and pathogenesis of the infection between animal species (Hines et al, 2014 ). Furthermore, the phenotypic changes that occur within MAP during infection (Everman et al, 2015 ) or during exposure to different environmental or host reservoirs (Cirillo et al, 1997 ; Patel et al, 2006 ; Alonso-Hearn et al, 2010 ) may result in ineffective vaccine efficacy. It is possible that due to the incorrect focus of vaccine development, chosen vaccine candidates are not representative of the most relevant antigens during the stages of Johne's disease in the animal.…”
Section: Introductionmentioning
confidence: 99%